Questionnaire survey of risk factors for recurrence of ocular inflammation in patients with uveitis after SARS-CoV-2 infection - Ma, Zonghui; Chi, Ying; Guo, Chunying; Zhang, Jing; Yang, Liu (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction During the COVID-19 pandemic in China, the proportion of patients with uveitis who were infected with SARS-CoV-2 increased greatly. The impact of SARS-CoV-2 infection on patients with uveitis has not been fully described. Methods A questionnaire on SARS-CoV-2 infection was sent to patients with uveitis to assess ocular and systemic conditions before and after infection. Chi-square analysis and multifactorial regression analysis were used to investigate the associations between each risk factor and the recurrence of uveitis after SARS-CoV-2 infection. Results One hundred thirty-nine patients with noninfectious uveitis completed the questionnaire; 114 (82.0%) had COVID-19, and 27 (23.7%) had recurrent or exacerbated uveitis after COVID-19. There was a higher rate of recurrence or aggravation of ocular inflammation in patients who developed severe COVID-19 symptoms (severe group 8/20 vs. nonsevere group 19/94). There were significant differences in the rates of recurrence and aggravation between the two groups of patients who differed in terms of ocular inflammatory activity within 3 months prior to SARS-CoV-2 infection (χ2 = 10.701, P=0.001), as well as in the rates of recurrence and aggravation after cessation of systemic immunomodulatory therapy. After multifactorial regression analysis, patients with active ocular inflammation within 3 months prior to SARS-CoV-2 infection had a greater risk of recurrence or exacerbation of uveitis after COVID-19 (OR=4.298, P=0.002). Conclusion The degree of ocular inflammatory activity within 3 months prior to SARS-CoV-2 infection may be a major factor influencing the recurrence or exacerbation of uveitis after infection. Interruption of medication should be minimized in patients with unstable inflammatory control.